Internal Fields in Multilayer WS2/MoS2 Heterostructures Epitaxially Grown on Sapphire Substrates. Issue 10 (19th April 2020) - Kim, Bora; Kim, Jayeong; Tsai, Po-Cheng; Kwon, Soyeong; Kim, Eunah; Yoon, Seokhyun; Lin, Shih-Yen; Kim, Dong-Wook
Abstract : In conventional 3D heterostructures, a gradual potential gradient in constituent layers and an abrupt potential discontinuity at heterointerfaces can appear. Studies of the electrostatic potential in 2D heterostructures require careful characterizations and analyses because the 2D materials have distinct physical characteristics compared with their 3D counterparts. Herein, three kinds of samples are prepared using sulfurization of metal layers on single‐crystalline sapphire substrates: WS2, MoS2, and WS2 /MoS2 . The surface potential ( V S ) of the samples is measured using Kelvin probe force microscopy. The light‐induced V S change in the stand‐alone trilayer (3L‐) WS2 (−63 mV) is much more notable than that in the 3L‐WS2 /3L‐MoS2 heterostructure (−12 mV). In contrast, the light‐induced V S change in the stand‐alone 3L‐MoS2 is positive and very large (≈200 mV). To explain these results, the potential and internal field distributions are proposed for both the stand‐alone (WS2 and MoS2 ) and heterostructure (WS2 /MoS2 ) samples. The polarity and magnitude of the internal field depend on the electronic interaction and screening from neighboring 2D layers and underlying substrates. Relative peak shifts of the Raman spectra of the samples are obtained and discussed, with consideration of the internal field effects. Abstract : The light‐induced surface potential change in the stand‐alone trilayer (3L‐) WS2 is much more notable than that in the 3L‐WS2 /3L‐MoS2 heterostructure. Such results are explained by internal electric fields in the constituent layers, determined by the electronic interaction and screening from neighboring layers and substrates. Raman spectra of the samples are discussed, with consideration of the internal field effects.